Detection of the termolábil toxin of Escherichia coli in fresh cheeses artesanales by means of PCR - Guerrero A., Daniza M. (2008)
This research was conducted using the Polymerase Chain Reaction (PCR) to detect heat-labile toxin of Escherichia coli in 24 fresh cheeses manufactured with cow and goat milk. The advantages of the PCR technique, over other analysis techniques, are reliability and rapidity to obtain the results. 24 samples of cheese (from cow and goat milk) were studied obtaining 58.33% of positive cases; 72.72% were positive with fresh goat milk and 46.16% of cow milk. Moreover, the X2 analysis showed, with 99% reliability, that the positive and negative results of the samples tested did not depend on the type of cheese used but did so on other factors, such as good manufacturing practices and standardization of the procedure.